MIGRASI ORANG TUA DAN KOGNITIF ANAK: ANALISIS DATA IFLS 2007 DAN 2014 - Lutvianti Zahra (Research Centre for Population, Indonesian Institute of Sciences, 2020)
Study about migration commonly focuses on the migrants themselves. However, some studies showed that migration also has economic and social impacts on their families, including their children. Cognitive ability is one of the fundamental aspects of child human capital development. This research aims to study the effect of parental migration on children's cognitive ability. This study employs longitudinal data from the Indonesian Family Life Survey (IFLS) in 2007 and 2014 analysed using the Pooled Least Square method and Instrumental Variable Two-Step Least Square (IV 2SLS). Descriptive results show a decline in the average cognitive score of children aged 14-25 years. Moreover, there were no significant differences in cognitive scores between children of migrant parents and non-migrant parents. Inferential results also found that parental migration did not significantly affect children's cognitive ability. Children's cognition is influenced by other characteristics such as age, sex, years of schooling, mother's education, per capita education expenditure, and area of residence.